Reformulating concepts and practices in the Third Age: an experience of U3A/UFMT - Rozendo, Adriano da Silva (2014)
The Universities of the third age (U3A) constitute a policy of attention towards senior citizens which is spread globally. Nowadays, seniors reach 60 years of age in good health, and better bio-psychosocial conditions of ageing. The new profile of elderly requires changes U3I’s models that should consider seniors as potential scholars and not just a mere informal guests, moving through the universities’ space.